Physicochemical and Sensory Properties of Red Dragon Fruit Jam Incorporated with Honey - Saiful Bharin, Nur Daleena Mastura; Abu Bakar, Fazleen Izzany (Enhanced Knowledge in Sciences and Technology, 2025)
This study focuses on the development and evaluation of red dragon fruit jam sweetened with honey, aiming to analyse its physicochemical properties and sensory acceptance. The research addresses the lack of tropical fruit jams in the Malaysian market by formulating a jam using ripe red dragon fruit and Tualang honey, a natural sweetener because of it has complicated sugar mixture primarily made up of oligosaccharides, fructose, glucose, and sucrose. These sugars affect the texture, crystallization, and overall quality of jam while also contributing to its sweetness. The primary objective is to assess the jam's quality through various physicochemical analysis, including total soluble solids (TSS), moisture content, pH, colour, and viscosity, alongside sensory evaluations with 50 untrained panellists using a 9-point hedonic scale. There are four formulations which are Control (Sugar Only), F1(Honey only), F2 (Honey+ sugar), and F3 (Honey + Sugar + Water) produced. Results indicated significant differences in pH across formulations, with values ranging from 3.357 (control) to 3.677 (honey + sugar + water), while TSS values were highest in the control formulation 55.73% compared to lower levels in honey-containing variants. Notably, the F2 formulation, which combines honey with a reduced amount of sugar, emerged as the most favourable in terms of both physicochemical properties and sensory acceptance. Moisture content also varied significantly; the control had 40.51% moisture against 56.94% for the formulation with added water. The incorporation of honey enhanced sensory attributes such as flavour complexity and texture but posed challenges for microbial stability due to higher moisture levels. Overall, this study successfully developed a red dragon fruit jam that meets consumer preferences for taste and quality, highlighting the potential of using tropical fruits in jam production and positioning honey as a viable alternative to traditional sweeteners. Further research is recommended to explore preservation techniques that enhance shelf life while maintaining product quality.